2022
DOI: 10.1088/1755-1315/950/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Digestive System of Little-black cormorant (Phalacrocorax sulcirostris) in Pulau Rambut Sanctuary

Abstract: Microplastics have been found in many seabirds in various areas in the world, but there has been no report from Indonesia. The objective of this research was to discover whether there were microplastics in the Indonesian Seabirds, represented by the Little-black cormorant (Phalacrocorax sulcirostris). The study site was Pulau Rambut Wildlife Sanctuary, a small island in Jakarta Bay, where a big colony of the cormorants’ nests together with other waterbirds. The gastrointestinal tract of a sample Little-black c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Apart from GIT, microplastic is also evident through inhalation in birds, such as a study by Takunaga [ 37 ], which found six microplastic particles in the lung tissue of wild birds from Japan. Three-hundred twenty particles/birds were extracted from GIT of the little black cormorant ( Phalacrocorax sulcirostris ) in Pulau Rambut Sanctuary, Indonesia [ 38 ]. Microplastics with an overall mean concentration of 11.9 ± 2.8 MPs/GIT were recovered from 8 species of birds in Florida, USA [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from GIT, microplastic is also evident through inhalation in birds, such as a study by Takunaga [ 37 ], which found six microplastic particles in the lung tissue of wild birds from Japan. Three-hundred twenty particles/birds were extracted from GIT of the little black cormorant ( Phalacrocorax sulcirostris ) in Pulau Rambut Sanctuary, Indonesia [ 38 ]. Microplastics with an overall mean concentration of 11.9 ± 2.8 MPs/GIT were recovered from 8 species of birds in Florida, USA [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Deoniziak et al [ 35 ] collected particles from the GIT of birds with sizes less than 1000 µm. A significant fraction (68.7%) of the extracted particles from GIT of the little black cormorant ( Phalacrocorax sulcirostris ) was in the range of 100–1000 μm [ 38 ] ( Table 1 ). The potential reason for relatively larger particles may be that larger particles are less movable in the GIT tract and hence trapped particles sink in different parts of the GIT, including crops, gizzards and intestines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particles from the gastrointestinal (GI) tracts of birds were collected by Zhu [ 49 ] and included 92.9% of particles smaller than 5 mm, and more than 90% in a study by Zhao [ 45 ], while Deoniziak [ 46 ] gathered bird GIT particles that were smaller than 1000 µm. The majority (68.7%) of little-black cormorants’ (Phalacrocorax sulcirostris) GIT-extracted particles were in the 100–1000 µm size range [ 50 ]. The fact that larger particles are less mobile in the GIT tract and consequently get stuck in different regions of the GIT, such as the stomach and gizzards, may be the cause of the significantly larger particle presence.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it causes various environmental damage and disturbances, such as environmental pollution by pesticides, soil erosion, a decrease in the diversity of local plant species, and disturbance to bird populations. Since many forest areas have been intensively converted to vegetable gardens, ecologically bird diversity is lower because the complexity of heterogeneous strata of vegetation determines the distribution of resources in bird communities and influences bird diversity (Paker et al 2014;Dinanti et al 2018;Hadisusanto et al 2022;Susanti et al 2022).…”
Section: Introductionmentioning
confidence: 99%